2019
DOI: 10.1097/md.0000000000016260
|View full text |Cite
|
Sign up to set email alerts
|

Acute compartment syndrome

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
45
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(48 citation statements)
references
References 56 publications
0
45
0
3
Order By: Relevance
“…Sport events such football can be one of the main causes for ACS in legs [25. ] In the group that underwent delayed fasciotomies, or fasciotomies performed after initial evacuation, they had higher Muscle excision (25 against 11%), amputation (31 versus 15%), and mortality (19 versus 5 percent) [6] that's why early intervention is important.…”
Section: Incidencementioning
confidence: 99%
See 3 more Smart Citations
“…Sport events such football can be one of the main causes for ACS in legs [25. ] In the group that underwent delayed fasciotomies, or fasciotomies performed after initial evacuation, they had higher Muscle excision (25 against 11%), amputation (31 versus 15%), and mortality (19 versus 5 percent) [6] that's why early intervention is important.…”
Section: Incidencementioning
confidence: 99%
“…More and more studies have shown that pressures greater than 30 mm Hg can be tolerated without causing harm, and it has been proposed that the difference between diastolic and compartment pressure, rather than an absolute threshold, be used as an indication for fasciotomy (diastolic pressure minus compartment pressure <30 mm Hg) [27].…”
Section: Incidencementioning
confidence: 99%
See 2 more Smart Citations
“…The initial suspicion of ACS is mostly inferred from observing its classical features, such as pain, pallor, pulselessness, paresthesia, poikilothermy, and paralysis [ 7 ]. It is verified either through invasive or non-invasive methods [ 8 , 9 , 10 ]. A typical invasive method is through measuring and calculating the difference between the mean arterial pressure and the intra-compartmental pressure (ICP) [ 11 ].…”
Section: Introductionmentioning
confidence: 99%